Complete genome sequence of Lactiplantibacillus plantarum strain GA_C_14 with potential characteristics applicable in the swine industry - Sumin Ryu; Hyunok Doo; Eun Sol Kim; Gi Beom Keum; Jinok Kwak; Sriniwas Pandey; Yejin Choi; Juyoun Kang; Sheena Kim; Hyeun Bum Kim; Ju-Hoon Lee (Journal of Animal Science and Technology)
In this study, the complete genome of Lactiplantibacillus plantarum strain GA_C_14 was sequenced and analyzed. We isolated the L. plantarum strain GA_C_14 from gajami sikhae, the Korean traditional food purchased from a local market in Gangneung, Korea. The genome of the L. plantarum strain GA_C_14 consisted of one circular chromosome (3,196,348bp) with a guanine + cytosine (GC) content of 44.7% and one circular plasmid (40,211bp) with a GC content of 38.9%. The genome annotation revealed 3,083 protein-coding sequences (CDSs), 67 tRNAs, as well as 16 rRNAs. The L. plantarum strain GA_C_14 possesses enzymes involved in vitamin B6 metabolism, such as gapB (EC 1.2.1.12), SerC (EC 2.6.1.52), dxs (EC 2.2.1.7), SerA (EC 1.1.1.95), PdxK (EC 2.7.1.35), and PdxH (EC 1.4.3.5). Moreover, the L. plantarum strain GA_C_14 harbors the beta-galactosidase (EC 3.2.1.23) enzyme required for synthesizing galactooligosaccharides (GOS). These results suggest that L. plantarum strain GA_C_14 could be utilized as a functional probiotic in the swine industry.